Vegetation compotition and structure of the pole community in the Girimanik natural forest area - Ardilla, Berliana Githa; Santhyami, Santhyami (JPBIO (Jurnal Pendidikan Biologi), 2025)
The pole is needed to increase ecological stability. This research analyzes the composition and structure of the pole community in the Girimanik Natural Forest Area, Setren Village, Slogohimo District, Wonogiri. The objective is to acquire a representative depiction of the pole community's structure and composition in this area. The research employed 25 plots, each measuring 10x10 m, covering a total area of 0.25 ha, strategically established in the region of the Girimanik Natural Forest Area. Data collection utilized the quadrat method. The findings revealed 41 species across 23 families, with a total basal area of 5.06 m². The species Schima walichii (DC.) Korth. and Quercus sundaica Rehder are the two most dominant species, exhibiting Important Value Indices of 40.41% and 37.33%, respectively. The Moraceae family encompasses the highest number of species, totaling five. The Diversity Index (H’) for pole species in the Girimanik Natural Forest Area is categorized as moderate, with an H’ value of 1. Conversely, the Dominance Index (C) is classified as high, with a value of 1.15. This study can be concluded that further research is needed to examine or find rare species of poles, so that more comprehensive conservation follow-up is needed for these rare species.